BIRTH ORDER AMONG NORTHERN INDIAN MEDICAL STUDENTS - Agarwal, Vinay; Garg, Sunil Kumar; Mishra, Megha Kulshreshtha; Chaudhary, Lalita (Indian Journal of Community Health, 2011)
Background: Birth order is claimed to be linked with academic achievement. However, many scientists do not accept it. Objective: To assess the association of birth order in North Indian medical students with number of attempts to cross the competition bar. Study design: Cross sectional study. Setting and participation: M.B.B.S. 1st year students of L.L.R.M. Medical College, Meerut. Statistical analysis used: Chi Square test. Methods: Enquiry of Birth order and number of attempts to crack the medical entrance examination from responded 360 medical students among 494 students admitted during 2005 – 2010. Results: The study revealed insignificant relationship between ages of entrance in medical college in both sexes. of 360 students responded 37% students were of first Birth order. Among those admitted in first attempt, 67% students were of first birth order and proportion of success in first attempt reduced with increasing birth order. Conclusion: Birth Order strongly influences academic achievements.